1981
DOI: 10.1055/s-2007-1023509
|View full text |Cite
|
Sign up to set email alerts
|

Conduit Repair for Complex Congenital Heart Disease with Pulmonary Atresia or Right Ventricular Outflow Tract Obstruction*,**

Abstract: From 1972 to 1981, 40 valved extracardiac conduits have been implanted to bridge the right ventricular outflow tract (RVOT) in 37 patients for different complex congenital cardiac anomalies. The patients ranged in age from 2 to 23 years (mean 8.5 years). Two Dacron prostheses with incorporated Lillehei-Kaster valves, 1 valveless Dacron conduit, 27 Hancock conduits, and 9 lonescu-Shiley conduits were chosen according to availability and the progress in conduit technology. Thirty-three patients had had up to 4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Specific problems encountered clinically include suboptimal hemodynamic performance and conduit kinking or compression. [5][6][7] In addition, fibrous peeling from the Dacron graft, which eventually results in valve dysfunction, has been reported previously. 5,7 To address these deficiencies, we undertook the development of a new biologic valved conduit: a bovine jugular vein graft with a retained native valve crosslinked with a naturally occurring crosslinking agent, genipin.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Specific problems encountered clinically include suboptimal hemodynamic performance and conduit kinking or compression. [5][6][7] In addition, fibrous peeling from the Dacron graft, which eventually results in valve dysfunction, has been reported previously. 5,7 To address these deficiencies, we undertook the development of a new biologic valved conduit: a bovine jugular vein graft with a retained native valve crosslinked with a naturally occurring crosslinking agent, genipin.…”
mentioning
confidence: 81%
“…T here is a great medical need for the use of external valved conduits in the repair of many congenital cardiac anomalies to reconstruct the right ventricular outflow tract (RVOT). [1][2][3][4][5][6][7][8][9] Currently available valved conduits can be divided into 2 primary categories: allograft and xenograft. For the reconstruction of the RVOT, Homann and associates 9 reported that allografts show significantly better longterm durability than xenografts, regardless of the age at implantation and the diameter of the valved conduit.…”
mentioning
confidence: 99%